Nodular kidney involvement in a patient with idiopathic Sweet's syndrome. (11th December 2013) - Daloul, Reem; Gupta, Sagar; Marin, Maria
Abstract : A 40-year-old previously healthy woman presented with a history of painful maculopapular rash, fever and diffuse arthralgia. The skin biopsy was consistent with Sweet's syndrome. Further workup with abdominal CT revealed bilateral hypoenhancing renal lesions involving the cortex and medulla, as well as terminal ileal thickening. Her renal function was preserved. The urinalysis revealed microscopic haematuria and sterile pyuria. Upper and lower gastrointestinal endoscopies were unremarkable and terminal ileal biopsy was normal. The evaluation for secondary causes of Sweet's syndrome was negative. She responded to corticosteroid therapy. A repeat abdominal CT scan two months later showed complete resolution of renal and ileal lesions. One year after the initial presentation the patient is doing well with no recurrent symptoms. We concluded that the abnormal renal findings were most likely due to sterile abscesses in the course of idiopathic Sweet's syndrome.